Impact of body mass index on worsening of diastolic function and impairment of left atrial strain in the general female urban population: a subanalysis of the Berlin female risk evaluation echocardiography follow-up study - Romero Dorta, Elena; Wolf, Adrian; Hübscher, Anne; Blaschke-Waluga, Daniela; Seeland, Ute; Crayen, Claudia; Bischoff, Sven; Mattig, Isabel; Dreger, Henryk; Stangl, Karl; Regitz-Zagrosek, Vera; Landmesser, Ulf; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The association of body mass index (BMI) with diastolic dysfunction (DD) is well described in the literature. However, there is conflicting evidence and long-term follow-up data regarding effects of BMI on preclinical DD and left atrial (LA) function are scarce, highlighting the importance of early detection tools, such as myocardial strain. Purpose The aim of our study was to prospectively analyze the impact of clinical and demographic parameters, especially of BMI, on worsening of diastolic function and left atrial strain (LAS) in an urban population of women with a low prevalence of cardiovascular risk factors. Methods and Results An extensive clinical and echocardiographic assessment comprising the analysis of phasic LAS using two-dimensional speckle-tracking echocardiography (2D STE) was performed in 258 participants of the Berlin Female Risk Evaluation (BEFRI) trial between October 2019 and December 2020 after a mean follow-up period of 6.8 years. We compared clinical and echocardiographic parameters stratifying women by BMI < or ≥25 kg/m2, and we analyzed the impact of demographic characteristics on the worsening of DD and LA mechanics in the longer-term follow-up using univariate and multivariate regression analyses. 248 women were suitable for echocardiographic analysis of LAS using 2D STE. After a mean follow-up time of 6.8 years, LA reservoir strain (LASr) and LA conduit strain (LAScd) were significantly reduced in participants with a BMI ≥25 kg/m2 compared with women with a BMI <25 kg/m2 at baseline (30 ± 8% vs. 38 ± 9%, p < 0.0001; −14 ± 7% vs. −22 ± 8%, p < 0.0001). 28% of the overweighted women presented a deterioration of diastolic function at the time of follow-up in contrast with only 7% of the group with a BMI <25 kg/m2 (p < 0.0001). BMI remained significantly associated with LAS reductions after adjustment for other risk factors in multivariate regression analyses. Conclusion Overweight and obesity are related to impaired LAS and to a worsening of diastolic function after a long-term follow-up in a cohort of randomly selected women.